Antibacterial activity of honey and Nigella sativa L. seed extracts against animal wound bacteria - Saïd Derbal; Abdellatif Niar (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
This study was designed to evaluate the antibacterial activity of Algerian honey and some extracts of Nigella sativa L. seeds against animal wound bacteria. To do this, the preparation of Nigella sativa L. seed extracts was carried out by macerating the seed powder in increasingly polar solvents (ethyl acetate, ethanol and methanol). The antibacterial activity of honey and Nigella sativa L. seed extracts against the bacterial isolates was studied by Agar Well Diffusion Assay. The results showed that the different honey concentrations (20%, 50%, 70% and 100% v/v) were found to be active against all the bacterial isolates. The different Nigella sativa L. seed extracts showed a variable activity at the concentration 300 mg/mL against the bacterial isolates. Ethanolic extract of Nigella sativa L. seeds was found to be active against all the bacterial isolates. Methanolic extract of Nigella sativa L. seeds was found to be active against all the bacterial isolates except Escherichia coli. Also, ethyl acetate extract of Nigella sativa L. seeds was found to be active against all the bacterial isolates except Enterococcus faecalis. In conclusion; Algerian honey (of the region of El-Eulma) and ethanolic extract of Nigella sativa L. seeds can be used as an alternative remedy for the treatment of different animal wounds.